2019
DOI: 10.1002/jper.19-0036
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and tooth loss have negative impact on dietary intake: A cross‐sectional study with stable coronary artery disease patients

Abstract: Background Despite the association between cardiovascular diseases and periodontitis, there are scarce data on the impact of oral health in the dietary intake of patients with coronary artery disease (CAD). The aim of this study was to assess the association between dietary intake with periodontitis and present teeth in individuals with stable CAD. Methods This cross‐sectional study included 115 patients with stable CAD (76 males, aged 61.0 ± 8.3 years) who were under cardiovascular care in an outpatient clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…These nutrients have an antioxidant effect [22], and adequate intake is necessary for the prevention of many non-communicable diseases (NCDs) including CVDs [23]. In fact, it is reported that having a greater number of present teeth (20) was associated with higher intake of fiber and total calories in patients with stable coronary artery disease [24]. Therefore, tooth loss, nutrition, and NCDs are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…These nutrients have an antioxidant effect [22], and adequate intake is necessary for the prevention of many non-communicable diseases (NCDs) including CVDs [23]. In fact, it is reported that having a greater number of present teeth (20) was associated with higher intake of fiber and total calories in patients with stable coronary artery disease [24]. Therefore, tooth loss, nutrition, and NCDs are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…Oral health is essential in preserving a healthy life in later years. Thus, oral health in the elderly population plays an important role in maintaining a balanced diet and healthy digestion and is closely related to systemic diseases [1,2]. Furthermore, with age the salivary glands undergo morphological changes, which gradually reduce saliva secretion.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of masticatory function and nutritional status on the general health and quality of life of the elderly has been extensively addressed in the literature [6,13,14]. A recent study has shown that patients with tooth loss above 20 teeth have lower consumption of healthy food and lower nutrient intake, which increases the risk of cardiovascular disease [13]. In addition, institutionalized elderly people who do not have posterior occlusal pairs and use a pasty diet were at higher risk of death after one year of follow-up [14].…”
Section: Discussionmentioning
confidence: 99%